2016
DOI: 10.1002/mren.201500044
|View full text |Cite
|
Sign up to set email alerts
|

Operation of Flexible Multiproduct Modular Continuous Polymerization Plants

Abstract: In this work, the operation of modular flexible continuous polymerization plants is investigated. For a benchmark problem (six products with an overall yearly demand of 20,000 t, two continuous production lines with modules that can be moved between the lines) that is defined by industrial speciality polymer producers, the optimal campaign planning problem is solved, minimizing the cost of cleaning and waste production. The results are compared to the production of the same portfolio of products in a batch pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The reactor investigated in this work has been designed to produce different polymers or different grades of a polymer and therefore studying the changeover between different products is of interest. Schoppmeyer et al have showed that the duration of the changeover has a strong influence on the economics of a process. Our approach to control the changeover scenario is to use a different cost function in this phase and to drive the properties of the product to a region which are considered as in‐spec for the new product (with some tolerance) in the shortest possible time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactor investigated in this work has been designed to produce different polymers or different grades of a polymer and therefore studying the changeover between different products is of interest. Schoppmeyer et al have showed that the duration of the changeover has a strong influence on the economics of a process. Our approach to control the changeover scenario is to use a different cost function in this phase and to drive the properties of the product to a region which are considered as in‐spec for the new product (with some tolerance) in the shortest possible time.…”
Section: Resultsmentioning
confidence: 99%
“…Schoppmeyer et al [ 32 ] have showed that the duration of the changeover has a strong infl uence on the economics of a process. Our approach to control the changeover scenario is to use a different cost function in this phase and to drive the properties of the product to a region which are considered as in-spec for the new product NMPC PF Figure 21.…”
Section: Changeover Scenariomentioning
confidence: 99%
“…For example, models have been successfully used to predict the transition of the solution polymerization of non-ionized acrylic acid [6], [7] or to study the impact of micromixing in the solution polymerization of methyl methacrylate (MMA) in a continuous stirred tank reactor (CSTR) [8]. This is a topic of primary interest from both academic and industrial points of view, as testified by several recent publications [6], [9], [10]. In particular, companies have interest in the production of large volumes of polymers always preserving their quality, in order not to alter their portfolio and ensure continuity in their business.…”
Section: Introductionmentioning
confidence: 99%
“…The logistic aspects of such plants are investigated in detail in ref. . The transfer of batch recipes from a batch plant to a plug‐flow reactor (PFR) is limited only by factors such as the geometry of the reactor and the minimum flow velocity for sufficient heat transfer and a sharp residence time distribution.…”
Section: Introductionmentioning
confidence: 99%